2011
DOI: 10.1083/jcb.201106048
|View full text |Cite
|
Sign up to set email alerts
|

Molecular networks linked by Moesin drive remodeling of the cell cortex during mitosis

Abstract: During mitosis, cortical Moesin activity is restricted to promote cell elongation and cytokinesis, but localized Moesin recruitment is necessary for polar bleb retraction and cortical relaxation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
131
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(135 citation statements)
references
References 55 publications
4
131
0
Order By: Relevance
“…In doing so, it facilitates spindle assembly [19,20]. At anaphase, Moesin is then deactivated at the poles by the phosphatase PP1 to induce local cortical softening to allow anaphase elongation and cell division [14,25]. At the same time, isotropic active Ect2 is relocated to the spindle midzone, where it concentrates RhoA-GTP, to drive furrowing [26].…”
Section: Ect2 and Erm Proteins In Mitotic Rounding And Cancer Metastasismentioning
confidence: 99%
“…In doing so, it facilitates spindle assembly [19,20]. At anaphase, Moesin is then deactivated at the poles by the phosphatase PP1 to induce local cortical softening to allow anaphase elongation and cell division [14,25]. At the same time, isotropic active Ect2 is relocated to the spindle midzone, where it concentrates RhoA-GTP, to drive furrowing [26].…”
Section: Ect2 and Erm Proteins In Mitotic Rounding And Cancer Metastasismentioning
confidence: 99%
“…However, their role in epithelial cell cytokinesis remains unknown, and it is unclear, for example, whether apical-basal segregation of PtdIns(4,5)P 2 and PtdIns(3,4,5)P 3 is preserved during epithelial cell mitosis. It is well established that, in Schizosaccharomyces pombe (Zhang et al, 2000), Drosophila S2 cells (Ben El Kadhi et al, 2011;Roubinet et al, 2011) and isolated mammalian cells (Abe et al, 2012;Dambournet et al, 2011;Emoto et al, 2005;Field et al, 2005;Kouranti et al, 2006), PtdIns(4,5)P 2 is the only phosphoinositide that is obviously enriched at the plasma membrane of the cleavage furrow. There, PtdIns(4,5)P 2 is essential for the recruitment of anillin (also known as ANLN in mammals and Scraps in Drosophila), which then interacts with components of the actin cytoskeleton, including F-actin, Myo II, RhoA, Ect2 [a guanine nucleotide exchange factor (GEF) for Rho GTPases] and septins (Box 1; Fig.…”
Section: Maintenance Of Polarity During Epithelial Cytokinesis?mentioning
confidence: 99%
“…ERMs harboring phosphomimetic or non-phosphorylatable residues are often used as dominant 'active' and 'inactive' proteins. However, recent studies have revealed that dephosphorylation of this site is important in many contexts, and in some cases, a cycle of phosphorylation and de-phosphorylation is actually essential to ERM activity (Kunda et al, 2012;Roubinet et al, 2011;Viswanatha et al, 2012). Such 'phosphocycling' of ezrin has recently been shown to be necessary for the formation of apical microvilli (Viswanatha et al, 2012).…”
Section: Introductionmentioning
confidence: 99%